Training tomorrow's doctors to explain 'medically unexplained' physical symptoms: An examination of UK medical educators' views of barriers and solutions. Issue 5 (May 2018) - Joyce, Emmeline; Cowing, Jennifer; Lazarus, Candice; Smith, Charlotte; Zenzuck, Victoria; Peters, Sarah
Highlights: FS are viewed as complex problems which attract negative attitudes from educators. FS are seen as common and serious, yet a low priority for the curriculum. Managed exposure and teaching by expert clinicians are recommended methods for FS. It is important to diminish the impact of the hidden curriculum on learning. Abstract: Objective: Co-occuring physical symptoms, unexplained by organic pathology (known as Functional Syndromes, FS), are common and disabling presentations. However, FS is absent or inconsistently taught within undergraduate medical training. This study investigates the reasons for this and identifies potential solutions to improved implementation. Methods: Twenty-eight medical educators from thirteen different UK medical schools participated in semi-structured interviews. Thematic analysis proceeded iteratively, and in parallel with data production. Results: Barriers to implementing FS training are beliefs about the complexity of FS, tutors' negative attitudes towards FS, and FS being perceived as a low priority for the curriculum. In parallel participants recognised FS as ubiquitous within medical practice and erroneously assumed it must be taught by someone. They recommended that students should learn about FS through managed exposure, but only if tutors' negative attitudes and behaviour are also addressed. Conclusion: Negative attitudes towards FS by educators prevents designing and delivering effective education on this common medical presentation. Whilst there is recognition of the need to implement FS training, recommendations are multifaceted. Practice implications: Increased liaison between students, patients and educators is necessary to develop more informed and effective teaching methods for trainee doctors about FS and in order to minimise the impact of the hidden curriculum.